ANALISIS KEKUATAN PAKU KELING PADA SUB- ASEMBLY KAMPAS REM BUS - Ryan Patra Wirabuana; Dwi Basuki Wibowo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Along with the increase of economic growth in Indonesia, the number of public transportation typed bus and freight truck also increased. The increase of buses and trucks creates problem namely increases the frequency of accidents every year. The accidents caused by brake failure that usually occurs as a result of brake oil is depleted. The quality of canvas that is not good or the release of brake lining from chassis brake (shoe brake) caused by rivets in order to fastening brake lining to the shoe brake is damaged / broken, but damaged rivets have never revealed. This happens because detail investigations about the caused of accidents rarely performed. To study the ability of rivet connection to sub-asembly of buses/ trucks brake in sustain the burden so rivet tensile test performed, brake lining sub-assembly compression test and validation of test results with FEM analysis. From the result of the test, the researcher got maximum shear of pressure of the rivet namely 4.891.753 kN, and the maximum pressure that received by each rivet on the loading conditions damaged the lining is 1,640 kN, 0.00003% of the maximum pressure of rivet. This result proves that the rivet have a greater shear strength than the brake.